Fa’aliyat Istikhdam al-Kitab al-Asasiy (Dirasah Taqwimiyyah fi Jami’ah Imam Bonjol al-Islamiyah al-Hukumiyyah Padang) - Afrina Refdianti; Afwan Afwan (Akademika: Jurnal Keagamaan dan Pendidikan, 2021)
Arabic language teachers and educational material compilers put all their skills and energy into enabling learners to master three competencies: linguistic, communicative and cultural. Text books, among other types of books, have a special place in the cultural development of this society. It is a repository of knowledge, a transmitter of culture, a center for the educational process, a means of communication between generations, and the main source of information for many teachers. The books used at the Islamic University of Imam Bonjol Padang are basic books for teaching Arabic to non-native speakers at Umm Al-Qura University, while the background of the students in this private university is diverse, some of them graduated from Islamic high school and some of them graduated from public high school. This study uses a mixed method, which combines a qualitative approach and a quantitative approach because it will present and analyze the effectiveness of the use of the book Teaching Arabic to Non-Native Speakers at the Islamic University of Imam Bonjol Padang. Based on the exposure and analysis of previous data regarding the effectiveness of the use of basic books (evaluation studies at the Islamic University of Imam Bonjol Padang), the results of the research are presented as follows: First: With regard to the contents of the basic book in terms of linguistic elements, language skills and culture. In terms of integration, this book takes into account the various language skills of listening, speaking, reading and writing. In terms of integration, this book also discusses all linguistic elements, namely sound, vocabulary, and structure. And in terms of grammar, there are structures that are presented based on the principle of similarity and the number of new structures in one lesson is appropriate, and training on structures is appropriate.